Chlorophyll a fluorescence in rice plants exposed of herbicides of group imidazolinone - Sousa,C.P. (2014)
The objective of this work was to investigate the injuries caused to the photosynthetic apparatus of three types of rice exposed to application of imidazolinone group herbicides. Two experiments were conducted using herbicides Imazethapyr+imazapic and Imazapyr+imazapic, in a split-plot experimental design, and a 3 x 3 factorial, with six replications. The first factor (A) consisted of the herbicide rates 0, 100 e 200 g ha-1 of Imazethapyr+imazapic and 0, 140 e 280 g ha-1 of Imazapyr+imazapic; factor B consisted of type of rice (cv. Puitá Inta CL, sensitive red rice ecotype and red rice ecotype with suspected herbicide tolerance to Imidazolinone). Chlorophyll a fluorescence parameters were evaluated in plants at 30 days after herbicide application, using a portable fluorometer (HandyPEA, Hanstech). The photosynthetic metabolism of cv. Puitá Inta CL was found to tolerate commercial dosages of both herbicides. High sensitivity to the herbicides was observed for the sensitive red rice ecotype, while the photosynthetic apparatus of red rice ecotype with suspected herbicide tolerance showed high tolerance to both herbicides applied at rates higher than the commercial rate. The application of chemical herbicides of the imidazolinone group on rice plants causes changes in the photosynthetic metabolism of plants, detected by evaluating the emission of transient chlorophyll a fluorescence. This method can be useful in helping detect resistance and/or tolerance of red rice plants to herbicides of the imidazolinone group.